2016
DOI: 10.2337/db16-0236
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Plasma Insulin Concentrations Are Associated With Changes in Hepatic Fatty Acid Synthesis and Partitioning Prior to Changes in Liver Fat Content in Healthy Adults

Abstract: Resistance to the action of insulin affects fatty acid delivery to the liver, fatty acid synthesis and oxidation within the liver, and triglyceride export from the liver. To understand the metabolic consequences of hepatic fatty acid synthesis, partitioning, oxidation, and net liver fat content in the fasted and postprandial states, we used stable-isotope tracer methodologies to study healthy men and women with varying degrees of insulin resistance before and after consumption of a mixed meal. Subjects were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 50 publications
1
61
3
Order By: Relevance
“…No direct assessment of hepatic CO 2 production has been undertaken in human subjects over the postprandial period; however plasma concentrations of 3-OHB have been measured. We have previously found mixed results with some of our studies showing a significantly lower (27) , similar (38) or higher (22) postprandial response of blood 3-OHB in insulin-resistant compared with insulin-sensitive individuals. We have also found that men have a notably lower postprandial 3-OHB concentration when compared with women (10) .…”
Section: Intra-hepatic Partitioning Of Fatty Acids: Oxidationcontrasting
confidence: 55%
See 2 more Smart Citations
“…No direct assessment of hepatic CO 2 production has been undertaken in human subjects over the postprandial period; however plasma concentrations of 3-OHB have been measured. We have previously found mixed results with some of our studies showing a significantly lower (27) , similar (38) or higher (22) postprandial response of blood 3-OHB in insulin-resistant compared with insulin-sensitive individuals. We have also found that men have a notably lower postprandial 3-OHB concentration when compared with women (10) .…”
Section: Intra-hepatic Partitioning Of Fatty Acids: Oxidationcontrasting
confidence: 55%
“…This will complement the suppression of fatty acid release from adipose tissue which is under the influence of insulin. Indeed, we have previously found strong inverse associations between hepatic DNL and plasma 3-OHB concentrations in the postprandial period in some, but not all, of our participants (10,38) suggesting a dissociation between the pathways. It could be speculated that some individuals have hepatic insulin resistance (which is not obvious at a systemic level) and this leads to a lack of suppression in ketone body production in the postprandial period.…”
Section: Intra-hepatic Partitioning Of Fatty Acids: Oxidationmentioning
confidence: 54%
See 1 more Smart Citation
“…The evening prior to the study day, subjects consumed deuterated water ( 2 H 2 O) (3 g/kg body water) and continued to consume 2 H 2 O during the course of the study day for the measurement of fasting and postprandial hepatic DNL. 24 On the study day, after an overnight fast and consumption of 2 H 2 O, subjects came to the Clinical Research Unit and a cannula was inserted into an antecubital vein and baseline (Time 0) blood and breathe samples taken. Participants were then fed a mixed test meal, consisting of 40 g Rice Krispies (Kelloggs, Manchester, UK), 200 g skimmed milk and a chocolate drink containing 40 g olive oil (40 g fat, 40 g carbohydrate).…”
Section: Compliancementioning
confidence: 99%
“…Increased hepatic DNL is also reported in hyperinsulinemic individuals, compared with those with normal glucose homeostasis (Pramfalk et al . ). Based on our observations, we propose that the acetate derived from inulin fermentation would have contrasting effects on hepatic lipid content depending on the metabolic health of the individual.…”
Section: Hepatic Metabolism Of Gut‐derived Short‐chain Fatty Acidsmentioning
confidence: 97%